Integrasi Kearifan Lokal dalam Pembelajaran Pendidikan Agama Islam - Reta Guspani; Hengki Satrisno; Yola Rizka; Bambang Irawan; Setia Rini Merliana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
The integration of local wisdom in Islamic Religious Education (PAI) is a strategic effort to strengthen the relevance of religious learning to students' lives. PAI learning not only focuses on ritual and doctrinal aspects, but also functions as a medium for character, moral, and socio-cultural identity formation. This study aims to analyze the role of local wisdom in PAI learning, its benefits in strengthening character, and the challenges of its implementation in the context of the Independent Curriculum. The research method uses a descriptive qualitative approach based on a literature review by examining the latest academic literature from 2018–2025. Data analysis was carried out through reduction, presentation, and conclusion drawing techniques, adopting the Miles and Huberman analysis model (Sugiyono, 2014). The results of the study indicate that the integration of local wisdom can increase the meaningfulness, contextuality, and effectiveness of PAI learning. Cultural values ​​such as mutual cooperation, courtesy, deliberation, and local religious traditions are in line with Islamic moral principles and can thus strengthen character formation. However, its implementation still faces several obstacles such as limited teacher cultural literacy, a lack of learning resources based on regional culture, and a lack of school support. This research confirms that the integration of local wisdom is highly relevant to the Independent Curriculum, which emphasizes contextual and project-based learning. Therefore, the integration of local wisdom in Islamic Religious Education (PAI) is a crucial approach to realizing an education that is humanistic, culturally rooted, and adaptive to changing times.